Gastric enterochromaffin-like (ECL) cells in hypergastrinaemic duodenal ulcer disease. Issue 2 (February 1990) - Coupe, M; Rees, H; Springer, C J; Bishop, A E; Morris, J A; Polak, J M; Calam, J
Abstract : Patients with hypergastrinaemic duodenal ulcer disease were studied to determine whether chronic moderate hypergastrinaemia produces hyperplasia of gastric enterochromaffin-like cells in man. Eight patients had peak postprandial plasma gastrin concentrations greater than 200 pmol/l, which is the 92nd percentile for patients with duodenal ulcer disease in this laboratory. The control group was eight patients with duodenal ulcers whose peak postprandial gastrin concentrations were less than 200 pmol/l. Basal and peak postprandial plasma gastrin concentrations were 107 (37) and 306 (66) pmol/l (mean (SEM] respectively in the hypergastrinaemic patients compared with 26 (4) and 137 (14) pmol/l respectively in the controls. There was no significant difference in the density of gastrin enterochromaffin-like cells between the two groups. The number of enterochromaffin-like cells per high power field was 53 (8) in the hypergastrinaemic patients compared with 50 (8) in the controls. We conclude that chronic moderate hypergastrinaemia does not produce hyperplasia of enterochromaffin-like cells in man. Our hypergastrinaemic group had plasma gastrin concentrations similar to, or greater than those reported during treatment with drugs such as omeprazole and histamine H2 receptor blockers.